Proteomics‐Based Soluble Urokinase Plasminogen Activator Receptor Levels and Long‐Term Cardiovascular Outcomes in Survivors of Breast Cancer: A UK Biobank Study - Adithya K. Yadalam; Chang Liu; Yan V. Sun; Anant Mandawat; Arshed A. Quyyumi; Salim S. Hayek (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Breast cancer is associated with increased risk for cardiovascular disease. suPAR (soluble urokinase plasminogen activator receptor) is an immune‐derived signaling glycoprotein implicated in the pathogenesis of atherosclerosis, as well as cancer, representing a shared risk factor for these conditions. We sought to examine whether elevated proteomics‐based suPAR levels are associated with cardiovascular death or incident coronary artery disease in survivors of breast cancer. Methods We leveraged Olink proteomics‐based measurement of suPAR levels in 845 female survivors of breast cancer without cardiovascular disease enrolled in the UK Biobank. We examined the association between suPAR levels and the primary composite end point of cardiovascular death or incident coronary artery disease with Fine and Gray competing‐risk regression, while accounting for the competing risk of noncardiovascular death and adjusted for clinical variables and C‐reactive protein levels. Results The median age was 61.0 years, and 96% were of White race. Over a median follow‐up of 13.4 years, 84 (9.9%) events of cardiovascular death or incident coronary artery disease occurred. After adjustment for demographics, traditional cardiovascular risk factors, and C‐reactive protein levels, proteomics‐based suPAR levels (per 1 SD) were independently associated with adverse cardiovascular outcome risk (subdistribution hazard ratio [sHR], 1.48 [95% CI, 1.16–1.88], P=0.002). When compared with participants in the lowest quartile of suPAR levels, those in the highest quartile had a 3‐fold increase in the risk of cardiovascular death or incident coronary artery disease (sHR, 3.08 [95% CI, 1.03–6.78], P=0.005). Conclusions In this cohort study of survivors of breast cancer, proteomics‐based suPAR levels were associated with an increased risk for adverse cardiovascular outcomes, highlighting the potential role of suPAR as a shared risk factor for cancer and cardiovascular disease.